Success Factors Evaluation in Construction Projects - et. al., Mohammad Hosein Ramin, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Nowadays, contractors, employers, and all stakeholders of a civil project looking to improve the quality level of construction in any type of project. This demands attention to some factors, which the project will be completed in the determined time and with an intended and predicted budget. Furthermore, the demands and expectations of stakeholders should be fulfilled. A project like this is called a successful project. Probably, the first issue in the implementation of civil projects is manpower resources, which are responsible for advancing the contractor and employer objectives. Therefore, paying attention to these resources and considering them more can improve the speed and quality of performance in the project. Considering their needs and motivation in a project can create energy and motivation in each of them individually, to improve performance. The aim of this study is success factors evaluation in the civil projects which is in terms of the purpose objectives and descriptive method. Statistical society of engineers that works in employer, consultant, and contractor teams of construction firms in Tehran, is in a site area in the residential project between 250 to 350 m2. To collect data, a five-item questionnaire was used. Questionnaires were distributed electronically among 170 engineers who work in the contractor, consultant, and employer teams in construction firms, and 149 questionnaires are answered. The final questionnaire results were obtained through Cronbach's alpha of 0.858. Based on these results, the five project success were ranked highest point to lowest, respectively, which contain employer and team satisfaction, project accidents, and project financial budgeting and scheduling. As seen in the results, the projects received very few scores in terms of scheduling that needs more attention.